Difficulties and Problems in the Implementation Phase of an Open Online Personalized Learning Environment for Vocational Education and Training for the Covid-19 period - Kolyvas, Georgios; Logaras, Chrystostomos; Kotsifakos, Dimitrios; Douligeris, Christos (Journal of Integrated Information Management, 2024)
Purpose - This article was formed in the context of a technical reflection on the difficulties and problems during the implementation phase of an Open Online Personalized Learning Environment for Vocational Education and Training. Design / methodology / approach - The implementation phase took place in the school period 2019 - 2021, and the application development continued in the school period 2020-2021. The main focus of this paper is threefold, namely: a) the evaluation of the deviation in achieving the design objectives, b) the detailed report on the difficulties and problems in the implementation phase, and, finally, c) the possible problems of future uses as the environment operates through the Panhellenic School Network. The online designed environment works with the existing digital infrastructure as a distance learning option. The specific educational material, taken exclusively from the Analytical Curriculum, was designed, and developed based on case studies and best practices so that, after various evaluations, it could be redesigned following the suggestions of students and teachers involved. Findings – The article, recording the difficulties, mediates as an assessment of the result, allows us to observe what has been achieved, and gives us the keys for similar future actions.